1999
DOI: 10.1063/1.124820
|View full text |Cite
|
Sign up to set email alerts
|

Switching properties of Pb(Nb, Zr, Ti)O3 capacitors using SrRuO3 electrodes

Abstract: We report on ferroelectric properties of polycrystalline sol-gel derived Pb(Nb, Zr, Ti)O3 (PNZT) thin films with SrRuO3 (SRO) electrodes. The processing temperature of the bottom electrode was varied between 550 and 850 °C. The polarization of the ferroelectric capacitors was dependent on the processing temperature of the bottom electrode. The capacitors exhibit low switching fields (40 kV/cm), high resistivity (1011 Ω cm at 3 V) and high remanent polarization values (19 μC/cm2 at 3 V), desirable properties fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…At 1 MHz no fatigue is observed up to 10 8 a͒ Author to whom correspondence should be addressed; electronic mail: pintilie@mpi-halle.mpg.de or pintilie@infim.ro cycles, in agreement with previous reports on PZT films with SRO electrodes. 9 However, a drastic decrease of the remnant polarization is observed for fatigue with lower frequencies.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…At 1 MHz no fatigue is observed up to 10 8 a͒ Author to whom correspondence should be addressed; electronic mail: pintilie@mpi-halle.mpg.de or pintilie@infim.ro cycles, in agreement with previous reports on PZT films with SRO electrodes. 9 However, a drastic decrease of the remnant polarization is observed for fatigue with lower frequencies.…”
mentioning
confidence: 97%
“…[2][3][4][5][6] It is generally accepted that the fatigue occurs in PZT films with platinum contacts, i.e., Pt/ PZT/Pt structures, and is absent if Pt is replaced with conductive oxides such as RuO 2 , IrO 2 , or SrRuO 3 ͑SRO͒. [7][8][9][10][11][12][13][14][15][16] A fatigue study performed at different frequencies on high quality epitaxial PZT films deposited on ͑100͒-oriented SrTiO 3 ͑STO͒ substrates with either a Pt or a SrRuO 3 ͑SRO͒ top electrode is reported on in this letter. It is shown that under certain conditions the fatigue occurred irrespective of the top electrode.…”
mentioning
confidence: 99%
“…Nevertheless, the thin films have a relatively low remanent polarization and high leakage current which are disadvantageous for application. It is well known that the properties of ferroelectric materials can be modified by the addition of dopants, in particular, the donor dopants such as Nb [11,12]. In general, the donor dopants increase the electrical resistance and enhance the remanent polarization of the ferroelectric materials.…”
Section: Introductionmentioning
confidence: 99%
“…SRO thin films grown by atomic layer control can be used in oxide multilayered heterostructure devices such as novel spin-polarized tunnel junctions and non-volatile ferroelectric random access memories [3,16,17]. For example, lead zirconate titanate (PZT) based ferroelectric capacitors with SRO as electrodes exhibit superior ferroelectric properties for potential non-volatile memory application.…”
Section: Introductionmentioning
confidence: 99%